Bioinformatic Analysis of the Genome of Infectious Salmon Anemia Virus Associated with Outbreaks with High Mortality in Chile - Cottet, L. (American Society for Microbiology (ASM), 2010)
The infectious salmon anemia virus (ISAV), an orthomyxovirus, is the major cause of outbreaks of high mortality rates in salmon in Chile. It has been proposed that the virulence of ISAV isolates lies mainly in hemagglutinin-esterase and fusion glycoproteins. However, based on current information, the contribution of other viral genes cannot be ruled out. To study this, we isolated and determined the complete coding sequence of two high-prevalence Chilean isolates associated with outbreaks of high mortality rates: ISAV752_09 and ISAV901_09. These isolates were compared to 15 Norwegian isolates that exhibit differences in their virulence. For this purpose, we performed bioinformatic analyses of (i) functional domains, (ii) specific mutations, (iii) Bayesian phylogenetics, and (iv) structural comparisons between ISAV and influenza virus glycoproteins by using molecular modeling. Phylogenetic analysis shows two genogroups for each protein, one of them containing the Chilean isolates. The gene sequence of the polymerase complex and nucleoprotein indicated that they are closely related to homologues from highly pathogenic Norwegian viruses. Notably, seven of the eight mutations that are present only in the Chilean isolates are on the polymerase complex and nucleoprotein. Structural modeling of hemagglutinin-esterase shows patches of variable residues on its surface. Fusion protein modeling shows that insertions are flexible regions that could affect proteolytic processing, increasing either the accessibility or the number of recognition sites for specific proteases. We found antigenic drift processes related to insertion into the isolated segment 5 of the ISAV752_09. Our results confirm the European origin of Chilean isolates to be the result of reassortments from Norwegian ancestors.